Penyuluhan Strategi Pemasaran STP untuk Meningkatkan Daya Saing Forum Komunikasi UMKM di Donokerto, Turi, Sleman, Yogyakarta - Sari, Niken Permata; Khairi, Ardhi; Sari, Utami Tunjung (Edumedia Solution, 2023)
The large number of MSME actors selling similar products can increase competition in the market. Therefore, to survive high competition, MSME business actors need to understand marketing strategies, especially segmentation, targeting, and positioning (STP). Partners in this community service program are members of the